Kepemimpinan Dalam Komunikasi Organisasi Dan Pengelolaan Konflik - Bakhtiar Masyah Halawa (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Conflict is an inevitable part of the dynamics of organizational life. An organization's success or failure in dealing with conflict depends heavily on the leadership style and communication patterns employed. This paper examines the crucial role of leadership in building healthy organizational communication and strategies for managing conflict constructively. Using a descriptive-analytical literature review method, this article finds that transformational and participatory leadership styles, supported by two-way (symmetrical) communication channels, significantly reduce the potential for destructive conflict. The analysis suggests that leaders do not need to eliminate conflict entirely, but rather redirect it into functional conflict that encourages innovation, transparency, and improved team performance.